Sebuah Fenomena Lesbianisme Mahasiswi Fakultas Ilmu Keolahragaan Pada Universitas Di Jakarta Timur - Sianturi, Tiurmaida; Zuryani, Nazrina; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
The purpose of this study was to analyze the phenomenon of lesbianism from the process, influencing factors and impacts for female students of the Faculty of Sports Science at a university in East Jakarta. This type of research is descriptive qualitative with habitus theory. The results of the study show that there are several factors that influence a person to become lesbianism, including internal and external factors. Internal factors are those that come from the individual, for example early attraction to other women (hormonal imbalance). While external factors come from outside the self, namely from the environment. The impact of lesbianism causes a new habitus to be born for lesbianism perpetrators, supported by the existence of capital (social, economic, cultural, and symbolic) owned by the female student.